Doing essays & assignments : - Greasley, Peter (Sage Publication, 2016)
Greasley's tips are backed up by a survey of lecturers, which highlights the things that markers are really looking for in students' work. However the book remains closely focused on its readers' needs, paying particular attention to areas in which students commonly struggle. Topics include: Introductions, conclusions and structuring; Finding and reading literature; Answering the question; Critical analysis and Referencing.